THE EVOLUTION OF STRATEGY: THINKING WAR FROM ANTIQUITY TO THE PRESENT/Beatrice Heuser - Vrey, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
The Evolution of Strategy: Thinking War from Antiquity to the Present is another welcome addition to the field of War Studies with its particular focus on strategy. The publication adds to a growing body of literature that explores new historical sources to anchor the theoretical departure of the work further, and attends to the emergent dilemmas of the future role(s) of the armed forces. At a time when critical stances about the utility of armed forces seem to have entered a growth period, The Evolution of Strategy contributes several well-argued perspectives to acknowledge and comment on questions related to the utility of armed coercion in contemporary times.